ln pursuit of Aryan Homeland (2nd Lithuanian Archaeological expedition in Afghanistan) - Aleksiejus Luchtanas; Ramunė Butrimaitė (Lietuvos Istorijos Studijos)
The second Lithuanian archaeological expedition in the province of Ghor is a constituent part of the long-term programme "Archaeological - Heritage Mission in Ghor Province, Afghanistan, 2007-2010." The programme is financed by the Ministry of Foreign Affairs, Republic of Lithuania. The programme is carried out by the Archaeological Projects Centre ANTIQUA. The partners of the project are the Ministry of National Defence of the Republic of Lithuania and Vilnius University.